Overexpression of CCDC69 activates p14ARF/MDM2/p53 pathway and confers cisplatin sensitivity - Long Cui; Fang Zhou; Cui Chen; Chi Chiu Wang (BMC, 2019)
Abstract Objectives The aim of the study is to explore the relationship between CCDC69 expression and resistance of ovarian cancer cells to cisplatin and reveal the underlying mechanism. Methods One hundred thirty five ovarian cancer patients with intact chemo-response information from The Cancer Genome Atlas (TCGA) database were included and analyzed. Stable CCDC69 overexpressing 293 and ovarian cancer A2780 cell lines were established and subjected to examine cell apoptosis and cell cycle distribution using CCK-8 assay and flow cytometry. Cell cycle and apoptosis pathway were evaluated by immunoblots. Stability of p14ARF/MDM2/p53 pathway related proteins were determined by half-life analysis and ubiquitination experiments. Results We found that CCDC69 expression was significantly higher in chemo-sensitive groups compared with chemo-resistant groups from TCGA database. High CCDC69 expression was associated longer survival. CCDC69 overexpressing 293 and A2780 cells with wildtype p53 and contributes to cisplatin sensitivity following treatment with cisplatin. We further found over-expression of CCDC69 activated p14ARF/MDM2/p53 pathway. Importantly, we also demonstrated that CCDC69 expression extended p53 and p14ARF protein half-life and shortened MDM2 protein half-life. Ubiquitination assay revealing a decrease in p14 ubiquitination in CCDC69 over-expression cells comparing to cells expressing empty vector. Conclusions It is tempting to conclude that targeting CCDC69 may play a role in cisplatin resistance.